Myth and Religion in the Traditional Dayak Way of Life: English - Dismas Kwirinus Dismas (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2023)
The focus of this paper is to explain myth and religion in the traditional Dayak community's view of life. Myths and religious systems in the life of the Dayak community have a fundamental role, which is the philosophy of life. Myths and religious systems form the basis of their social and cultural life. Myths and religious systems not only have a decisive role in the life of the Dayak community, but are also an expression of their way of being in this world. This paper aims to describe and analyze the elements of culture, as well as to provide an anthropological-philosophical contribution regarding ancient myths and religions in the Dayak community's view of life. The author uses a descriptive qualitative method that produces data in the form of words and in writing or verbally from the people and observed behavior. As for the findings of this paper, that ancient myths and religions are still alive and have no small influence in today's modern society. The introduction of ancient traditional societies enriches the consciousness of modern humans to know themselves better. Modern humans draw a variety of ancient